Traditional knowledge: issues and challenges - Ismail, Zahora; Hassan, Suziana; Muning, Maznah; Gerten, Adam Haris (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
Traditional knowledge in Malaysia could be found in many different forms. It could be traced in the form of cultural practices, beliefs, language, foods and others. Although development would one way or another substitute what is left of the original version of the traditional knowledge practiced by the different community that exists, there are still communities that has remained intact with their indigenous knowledge on daily basis, as a necessity for their lives; consciously, and unconsciously. The loss of a traditional knowledge, although presumably would not make a big an effect big enough to imminently jeopardize the community involved, but the loss of identity and the loss of a more natural way of life should be concern. We could not predict where or how development would take us, but we could safely say that the traditional knowledge has so far work effectively in guiding people through their lives. It is noteworthy that the value of local traditional knowledge to conservation is increasing recognized, but traditional knowledge rapidly loss as indigenous livelihoods change. Within this particular context, the paper aims to look at selected studies that had been done in Malaysia in preserving traditional knowledge. The paper will analyse some pertinent issues and challenges face in obtaining the knowledge of the local traditional people in this country.